Ta’tsir Barnamaj Tazwid al-Mufradat ala Kafa’ah Kitabah al-Insya’: The Effect of the Vocabulary Enrichment Program on Composition Writing Efficiency - Qibtiyah, Luthfatul; Romlah, Siti; Amini, Izzat (ELOQUENCE : Journal of Foreign Language, 2023)
Background: The Tazwidul Mufrodat program is a program that is carried out to add new vocabulary and will later be developed into work both in conversation and in written form. Purpose: This article aims to determine the effect and how much influence the Tazwidul Mufrodat program has on the ability to write insya’ intensive semester IV students. Method: This research used the quantitative approach with the type of causal link. The population in this article were 53 intensive female student. Data collection tecniques used are questionnaires, written tests, observation the result of tazwidul mufrodat’s reseach on the ability to write insya’, a fourth semester intensive student at the Al-Amien Prenduan institute. Results and Discussion: Based on the results of the calculation of the F test, it was found that the calculated F value was 2,891. So t count > t table (6,298 > 1,671). Then the tazwidul mufrodat program for intensive famele student in fourth semester at institute Dirosat Islamiyah Al-Amien Prenduan and the R Square value shows a value of 0.054 meaning that the tazwidul mufrodat program has an effect of 0.054 or 5.4 % while others are influenced by other factors outside the independent variable. This shows significance 0.000 < 0.05, it can be concluded that Ha is rejected and Ho is accepted.